XX зууны эхэн үе ба XXI зууны эхэн үеийн нийгмийн байдал, яруу найраг, шинэчлэл, хэлний зарим асуудал: Some issues on social status, poetry, its language and renovation in the beginning of the 20th century - Д., Галбаатар (Mongolian Studies, 2023)
The development of modern Mongolian poetry is commonly described as coinciding with the emergence of revolutionary songs in 1921. Nonetheless, a more interesting and appropriate understanding of 20th-century poetry, and specifically the content and linguistic aspects of song lyrics, may be achieved by studying these as directly connected to the independence movement of 1911 and the conventions of the period that preceded it.